Kritik Sosial Generasi Z dalam Konten TikTok Pray For Sumatra: Analisis Narasi Bencana dan Kepemimpinan: Analisis Narasi Bencana dan Kepemimpinan - Cecep Ahmad Topa (Journal of Citizenship, 2026)
Abstract This study analyzes how Generation Z uses TikTok to create critical narratives about the November 2025 flood disaster in Sumatra and respond to government leadership, rather than simply expressing sympathy. Using a qualitative approach with a focus on narrative analysis, this study explores five TikTok videos using the hashtag #PrayForSumatra created by young content creators aged 17 to 25. The results of this study show that the content is not only about prayer and loss, but also contains social criticism organized in six recurring narrative patterns. These findings confirm that Generation Z is not only a passive and empathetic audience, but also an active communicator, utilizing digital media to change the way society understands the disaster, from a mere "natural tragedy" to a "policy failure that requires structural accountability" from the government. This study ultimately highlights the importance of critical literacy and digital activism of Generation Z in responding to the disaster, with TikTok serving as a means of narrative resistance to the official explanation from the government. Keywords: Generation Z, TikTok, Narrative Analysis, Disaster Communication, Leadership Crisis. Abstrak Penelitian ini meneliti cara Generasi Z menciptakan cerita yang menyoroti masalah terkait banjir di Sumatra pada November 2025 lewat TikTok, sekaligus merespons cara pemerintah bertindak, bukan sekadar menunjukkan rasa sedih. Dengan melihat cara narasi dibuat, studi ini mengamati lima video TikTok bertagar #PrayForSumatra yang dibuat anak muda berumur 17 sampai 25 tahun. Hasilnya, video-video itu bukan hanya berisi doa dan kesedihan, tetapi juga punya kritik sosial dalam enam pola narasi yang muncul berulang. Temuan ini menunjukkan Generasi Z bukan cuma orang yang diam dan ikut merasakan, tapi juga orang yang aktif bicara pakai internet untuk mengubah pandangan orang tentang bencana, dari sekadar "kejadian alam" jadi "kebijakan yang gagal dan pemerintah harus bertanggung jawab". Studi ini akhirnya menekankan pentingnya Generasi Z bisa berpikir kritis dan aktif di internet saat ada bencana, dengan TikTok menjadi cara untuk melawan cerita resmi dari pemerintah. Kata kunci: Generasi Z, TikTok, Analisis Narasi, Komunikasi Bencana, Krisis kepemimpinan.